Analisis Perbedaan Tingkat Fertilitas Pekerja Wanita di Sektor Formal dan Informal di Kabupaten Badung - Saraswati, Dewa Ayu Tri; Dewi, Made Heny Urmila (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2019)
The purpose of this study is to find out whether the socio-economic demography of women workers in the formal and informal sectors and to determine the level of fertility of female workers in the formal and informal sector in Badung regency. This research was conducted in Badung regency of Bali Province. Number of samples taken in the formal sector is 49 people and the informal sector is 51 people in total is 100 people, with Proportionate sratified random sampling method. Based on results it was found that there was a significant difference between the fertility rate of female workers in the formal sector and the level of fertility of workers informal sector. This suggests that socio-economic factors of demography greatly affect fertility. The higher level of education, income, and social status of a person the tendency to have more children will decrease. Similarly, the first married person has a negative relationship to fertility. People who choose to get married in the same time as ideal. The greate period of someone's respiration then the possibility of having more children the higher will affect fertility. The first marriage age will be an alternative to regulate the birth distance other than KB.